The game as a factor of creativity (based on the Konstantin Moskalets’s essay «The game continues») (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article examines the ideological and artistic functions of the concept of «game» in the Konstantin Moskalets’s essay «The game continues». The game is interpreted by the author as a factor and the highest expression of creativity, the means of overcoming absurdity of the modern world, the necessary component of the artist’s life   in harmony with himself, the meaning of his life.  Creativity is reflected as the rank, the  mission of artist, who should seek the meaning of life in the sensory space of the game, creating it  himself, despite the unfavorable conditions, time, totalitarian pressure, indifference of others.
Keywords: essay; game; creativity